2021
DOI: 10.1111/jog.14680
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reaction to pegylated liposomal doxorubicin administration for Mullerian carcinoma in Japanese women

Abstract: Aim PEGylated liposomal doxorubicin (PLD) is a therapeutic agent for gynecological malignancy. Hypersensitivity reaction (HSR) is a major adverse effect that usually disappears after halting administration of PLD. Premedication is usually not necessary before administration of PLD to prevent HSR. Here, we evaluated the frequency of HSR during administration of PLD following premedication in Japanese women. Methods We performed PLD administration in 78 patients (386 cycles) between 2013 and 2018. Granisetron hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the current study, patients experienced a fairly high incidence rate of HSRs (64.3%). In contrast, research by Alberts et al and Yamaguchi et al (2021) reported very low frequencies of HSRs between 7 and 9% ( Alberts and Garcia, 1997 ). In other research, Gabizon et al (1994) reported a frequency of 25%, while Castells et al (2008) reported that 4 of 5 patients experienced HSR.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the current study, patients experienced a fairly high incidence rate of HSRs (64.3%). In contrast, research by Alberts et al and Yamaguchi et al (2021) reported very low frequencies of HSRs between 7 and 9% ( Alberts and Garcia, 1997 ). In other research, Gabizon et al (1994) reported a frequency of 25%, while Castells et al (2008) reported that 4 of 5 patients experienced HSR.…”
Section: Discussionmentioning
confidence: 87%
“…Premedication is usually not necessary before the administration of PLD to prevent HSRs ( Yamaguchi et al, 2021 ). However, the incidence rate of PLD-induced HSR varies widely across existing reports.…”
Section: Discussionmentioning
confidence: 99%